2015
DOI: 10.13075/mp.5893.00142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of work-related musculoskeletal disorders among physical therapists

Abstract: Background: Health professions like dentistry, nursing and physical therapy have been reported at high risk for developing workrelated musculoskeletal disorders. Results of studies conducted in these occupational groups may help formulate prevention strategies. However, no such data among physical therapists has been reported in India. Material and Methods: We conducted an online survey among 100 physiotherapists in Delhi. Results: The response rate was 75%. The prevalence of work-related musculoskeletal disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 27 publications
3
35
1
2
Order By: Relevance
“…29,30 This has been attributed to their smaller body structure, lower muscle tone and higher stress levels as compared males. [31][32][33] Neck and lower back were reported to be more prone to pain and increased risk of developing musculoskeletal disorders by the respondents. Our findings are in line with the results of previous studies showing that neck, shoulder and lower back pain was commonly reported among dental students.…”
Section: Discussionmentioning
confidence: 96%
“…29,30 This has been attributed to their smaller body structure, lower muscle tone and higher stress levels as compared males. [31][32][33] Neck and lower back were reported to be more prone to pain and increased risk of developing musculoskeletal disorders by the respondents. Our findings are in line with the results of previous studies showing that neck, shoulder and lower back pain was commonly reported among dental students.…”
Section: Discussionmentioning
confidence: 96%
“…32 As populações mais pobres têm sua saúde afetada pelos altos índices de violência, pela falta de investimento e pela dificuldade de acesso à educação, saneamento, habitação, transporte, serviços de saúde e alimentação adequada. 33 Os estudos de Iqbal 23 Além de questões de infraestrutura, os fatores psicossociais influenciam na saúde da população. A desigualdade de renda diminui a coesão e a confiança social, aumentando os níveis de estresse, depressão e as taxas de criminalidade.…”
Section: Discussionunclassified
“…For upper limb work, repeated cycles are performed in equal or less than 30 s or more than 2-4 times/min for at least 4 h during a work-shift [21]. Thus, the issues of ergonomics and proper techniques used during manual therapy are of great importance [23], as well as prevention of musculoskeletal disorders by increasing the activity and physical fitness of therapists [18,24] and developing an occupational hazard data sheet for the massage therapist profession [25].…”
Section: Ijomeh 2018;31(5) 682mentioning
confidence: 99%